Small molecule activation by frustrated Lewis pairs. - Travis, A; Binding, S; Zaher, H; Arnold, T; Buffet, J; O'Hare, D (2013)
A series of frustrated Lewis pairs (FLPs) based on the Lewis acids tris(perchloroaryl)borane (BAr(Cl)), and tris(2,2',2''-perfluorobiphenyl)borane (PBB) and trialkylphosphines were prepared; their ability to effect the heterolytic cleavage of dihydrogen, insert carbon dioxide into the borohydride, and reduce the resulting formatoborate to methanol were studied. Additionally, the insertion of CO(2) into a B-OH bond is explored with the ultimate aim of developing a homogeneous, catalytic preparation of carbonates. The compound [PBB-OH][H-P((t)Bu)(3)] was characterised by single crystal X-ray crystallography.